Evaluation of F1 hybrids of chile (Capsicum annuum) from crosses between parents focused on obtaining varieties such as "Blocky or Bell Pepper" (Repertorio Científico, 2022)
The production of new varieties for agriculture is very important to be more profitable and productive, in addition to being able to adapt to climate change. For their part, blocky varieties are growing in consumer demand in Costa Rica. The objective of this research was to carry out the evaluation of F1 hybrids of C.annum focused on obtaining local seed of varieties such as "Bell Pepper or Blocky", yellow, red and orange; also elucidate some inheritance traits. Also evaluate commercial varieties and progenies obtained by self-pollination in commercial varieties. A field evaluation of the F1 hybrids was carried out with a Latin square experimental design, with 4 blocks and 4 repetitions per evaluated progeny, coming from the initial crosses. To analyze the data, an ANOVA was performed with a confidence level of p
Keywords: hybrid; chili; blocky; heterosis; progeny